2019
DOI: 10.3390/molecules24173184
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effects of Pyrimidine Functional Group Switches on Acyclic Fleximer Analogues for Antiviral Activity

Abstract: Due to their ability to inhibit viral DNA or RNA replication, nucleoside analogues have been used for decades as potent antiviral therapeutics. However, one of the major limitations of nucleoside analogues is the development of antiviral resistance. In that regard, flexible nucleoside analogues known as “fleximers” have garnered attention over the years due to their ability to survey different amino acids in enzyme binding sites, thus overcoming the potential development of antiviral resistance. Acyclic flexim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
(60 reference statements)
0
8
0
Order By: Relevance
“… 182 Combining the split purine base with an acyclic glycon (as found in the anti-herpesvirus drug acyclovir) has led to promising activity against members of different RNA virus families, including Filo -, Flavi-, and Coronaviridae . 184 186 Still, the mechanism of action remains subject of studies and although it has been shown that fleximer-triphosphates can be substrates for nucleic acid polymerases, 187 it is still unclear whether the antiviral activity of acyclic fleximers is achieved via this mechanism. Mutagenic properties similar to ribavirin etc.…”
Section: Targeting Viral Rna Synthesis With Direct-acting Antiviral Nmentioning
confidence: 99%
“… 182 Combining the split purine base with an acyclic glycon (as found in the anti-herpesvirus drug acyclovir) has led to promising activity against members of different RNA virus families, including Filo -, Flavi-, and Coronaviridae . 184 186 Still, the mechanism of action remains subject of studies and although it has been shown that fleximer-triphosphates can be substrates for nucleic acid polymerases, 187 it is still unclear whether the antiviral activity of acyclic fleximers is achieved via this mechanism. Mutagenic properties similar to ribavirin etc.…”
Section: Targeting Viral Rna Synthesis With Direct-acting Antiviral Nmentioning
confidence: 99%
“…L-carnitine plays an essential role in the production of energy and fatty acid metabolism. This can further improve and control the immune-modulatory functions in diabetic patients, neuropathic pain, and other liver and kidney-related diseases [66,67]. Thus, carnitine could be a good option to prevent the harm caused by COVID-19.…”
Section: Importance Of Dietary Supplementsmentioning
confidence: 99%
“…Commercially available DNA polymerases were used: endonuclease-free A detailed study by Seley-Radtke and coworkers revealed the relationships between the structure of functionalized pyrimidine ring and the activity of imidazole-pyrimidine fleximers against the Ebola virus, as well as mentioned some unpublished data on antiflavivirus properties of the "classic" fleximers. 24 The correlation between the biological properties and structural features of "flexible" nucleobases was discussed in a monograph published in 2014. 28 Acyclic bitriazole nucleosides 24 (Scheme 10) exhibited antiproliferative activity against the drug-resistant pancreatic cancer cell line MIA PaCa-2, which is associated with caspase-dependent apoptosis.…”
Section: The Biological Activity Of Fleximersmentioning
confidence: 99%
“… 22 This could, for example, explain the unexpected earlier observation: fleximer guanosine analog 2 inhibited S- adenosyl- L-homocysteine hydrolase (EC 3.3.1.1) – an enzyme that is specific for adenosine, while fleximer 1 (an adenosine analog) did not interact with this enzyme. 23 Both ribosides and acyclic fleximers 24 predominantly existed in their anti conformations in solutions (compounds 35 – 38 , Fig. 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation